Ultraviolet emission and electron spin characteristics of Th(C2O4)2·xH2O:Gd3+. (15th September 2020) - Gupta, Santosh K.; Rajeshwari, B.; Achary, S. N.; Kadam, R. M.
Abstract : UV emitting Gd 3+ doped phosphors have recently attracted significant attention among materials scientists owing to their important applications in the areas of photothermal therapy, transilluminators and sensitizer based luminescent phosphors. Abstract : Ultraviolet emitting Gd 3+ doped phosphors have recently attracted significant attention from the optical science community owing to their important applications in the areas of photothermal therapy, transilluminators and sensitizer based photoluminescent phosphors (PLPs). It was found in several previous studies that the annealing temperature and water content has a profound influence on the emission intensity and luminescence lifetime of PLPs. In this context, we have synthesized Th(C2 O4 )2 ·6H2 O:Gd 3+ (TOHG) and characterized it using photoluminescence (PL) and electron paramagnetic resonance (EPR) spectroscopy. Emission spectroscopy showed the presence of a singular peak at 311 nm due to an electric dipole transition, suggesting the extremely low symmetry around Gd 3+ in TOHG. Luminescence lifetime measurements suggested two different local environments of Gd 3+ in TOHG; the shorter lived one (S) is closer to oxygen vacancies and the longer lived one (L) is further away from the oxygen vacancies. The time resolved emission spectrum shows a slightly different peak profile for S and L. The EPR spectra of TOHG suggested that Gd 3+ is situated in a nearly eight-fold coordination of oxygen (cubic coordination) at the Th 4+ ion. Furthermore, we carried out thermal treatment of TOHG at 250 °C which led to Th(C2 O4 )2 ·2H2 O:Gd 3+ (TODG) which on further annealing at 300 °C was converted into anhydrous thorium oxalate (TOAG). X-ray diffraction analysis suggested a triclinic lattice structure for TOHG and a monoclinic and orientationally disordered structure for TOAG. The PL emission intensity and excited state lifetime were found to be greater for TOAG due to the absence of the non-radiative transition provided by water molecules. The EPR spectra of TOAG suggested lowering of the site symmetry to rhombic symmetry in TOAG. This is in agreement with our structural analysis. Such a complete spectrum of work wherein the structure, excited state dynamics and spin properties of Gd 3+ were investigated will open up a new avenue into gadolinium photophysics, particularly for researchers to explore actinide oxalate with a view to thermally tuning its properties.